Morphological and Molecular Characterization of a New Mycobacterium avium Subsp. paratuberculosis S-Type Strain Genotype in Goats - Scherrer, Simone; Stephan, Roger; Zumthor, Jon Paulin; Kipar, Anja; Seehusen, Frauke (Frontiers in Veterinary Science, 2019)
Paratuberculosis is a chronic bacterial disease of global importance mainly in domestic and wild ruminants, caused by Mycobacterium avium subsp. paratuberculosis (MAP). In goats, paratuberculosis is mostly caused by the “C-type” (cattle) and in a few cases by the “S-type” (sheep) strain of MAP. In 2017, a caprine S-type III isolate with a new VNTR profile was identified in a Swiss alpine region. In 2018, new caprine isolates with the same novel VNTR profile originating from a farm of a close by neighboring valley were analyzed. Here we report on this MAP S-type III outbreak in a Swiss dairy goat farm in which we investigated the pathological changes, distribution and genotype of MAP in the tissues homogenates. Full necropsy and histological examination were undertaken on two female adult goats with a history of weight loss and intermitting diarrhea. Routine and special stains were applied to characterize the morphological changes. DNA was extracted from 33 different tissue samples and tested for MAP by real-time qPCR targeting IS900 and F57. Subtyping was performed, using the variable number tandem repeats (VNTR) and mycobacterial interspersed repetitive units (MIRU) approach. The goats showed moderate to marked emaciation and displayed typical clinical features of paratuberculosis. A moderate granulomatous enteritis and regional lymphadenitis with a small to moderate number of acid-fast bacteria within macrophages was detected. MAP detection was mainly restricted to the gastrointestinal tract, mesenteric and hepatic lymph nodes. Subtyping the S-type isolates using a panel of eight established MIRU-VNTR loci identified a new genotype, INMV 218.